The Impact and Effectiveness of E-Learning on Teaching and Learning - Elcullada Encarnacion, Riah F.; Galang, Annjeannette Alain D.; Hallar, Byron Joseph A. (International Journal of Computing Sciences Research, 2020)
Purpose – This paper presents research findings on the effectiveness and impact of E-Learning to the teaching and learning process of the Undergraduate Program (UGP) and General Foundation Program (GFP) at Oman Tourism College in Muscat, Sultanate of Oman. Method – Teacher and student experience on E-Learning were evaluated by utilizing mixed methodology through online survey. Five criteria of effectiveness were established and used to assess E-Learning. The study determined the consensus measure and target consensus measure of teachers and students on the effectiveness of E-Learning employing the five factors. The study also examined whether students and teachers differ in their perceptions on E-Learning. The effects of E-Learning on teaching methodology and learning styles were also investigated. Results – Teachers and students appeared to be in agreement on their perceptions on E-learning and provided higher ratings on E-Learning based on the five criteria of effectiveness. E-Learning was viewed favorably by teachers and students as an effective tool to enhance the delivery of instruction and develop knowledge acquisition skills through transfer of learning. Conclusion –E-Learning can be considered as one of the best strategies to be adopted for teaching and learning. The researchers assert that the provision of education can no longer be restricted within a single campus but can be extended throughout the country through distance learning and integration of E-Learning solutions. Recommendation – It is highly recommended that further study can be conducted to include other Higher Education Institutions in Oman in order to form a more concrete knowledge-based plan in creating E-Learning strategies. Practical Implication – E-Learning could potentially shape the future of education by advancing the traditional classroom setting into the web. There is a need for the entire academic community to ensure that the factors of e-learning effectiveness are delivered adequately and the utilization of e-learning must be evaluated regularly.